The association of objectively measured physical activity and sedentary behavior with skeletal muscle strength and muscle power in older adults: A systematic review and meta-analysis - Ramsey, Keenan A. (Elsevier Ireland Ltd, 2022)
10.1016/j.arr.2021.101266